Metabolic syndrome, adipokines and ghrelin in overweight and obese schoolchildren: results of a 1-year lifestyle intervention programme - Carla Pedrosa (2011)
The aim of this study was to evaluate the effect of a lifestyle intervention programme (nutrition and exercise counselling) on metabolic syndrome (MS) components, adipokines (leptin, adiponectin) and ghrelin levels in overweight children. A total of 61 overweight children aged 7-9 years (>= 85th body mass index (BMI) percentile; 27 boys/34 girls) were randomly assigned and completed a 1-year individual (IT) or group-based treatment (GT). Anthropometric and biochemical parameters were assessed at baseline, at 6 months and at 1 year. Twenty-two normal weight children (< 85th BMI percentile; 7-9 years old; 13 boys/nine girls) were also evaluated at baseline. Insulin resistance (IR) was determined by the homeostasis model assessment of IR (HOMA-IR). Overweight children presented significantly higher blood pressure, triglycerides, apolipoprotein B, insulin, HOMA-IR, leptin, C-reactive protein and homocysteine levels, while apolipoprotein A-I was significantly lower. At baseline, MS was present in ten overweight children, of which only five maintained it at 1 year. Leptin and ghrelin levels were associated with IR and MS components. MS was predicted by apolipoprotein A-I, insulin and pre-puberty. The lifestyle intervention led to a significant improvement in standard deviation score of BMI, waist circumference/height ratio and lipid profile. Changes in insulin, HOMA-IR, leptin and adiponectin were not significant. Ghrelin behaved differently between IT and GT. The GT intervention seems to be more successful, with a decrease in BMI Z-score and an improvement of metabolic parameters. In conclusion, overweight children have multiple risk factors associated with MS. A lifestyle intervention programme seems to be an effective mean for reducing obesity and MS components and improving adipokines concentrations.